1987
DOI: 10.1177/00220345870660021001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Sex-related Differences in the Structure of Submandibular Glycoconjugates

Abstract: Structures of oligosaccharides in submandibular glycoproteins were evaluated in situ. Sections of fixed paraffin-embedded glands from rats, mice, hamsters, sheep, and man were stained with a battery of lectins conjugated to horseradish peroxidase in conjunction with other methods, such as digestion with sialidase with or without prior saponification and/or periodate oxidation. Secretory glycoproteins showed a characteristic lectin binding pattern for each genus. Sialoglycoconjugates were detected in acinar cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…The nine lectins used here were selected for their ability to distinguish the different types of cells present histochemically in the rat submandibular gland. The staining with UEA-I, LFA, PNA, LCA, DBA, and SBA (see Table 1) corresponded to previous studies (Schulte, 1987; Schulte and Spicer, 1984). Our ble to fine discrepancies in their preferred sugars with regard to both penultimate sugar and anomeric configuration (Spicer and Schulte, 1992;Watanabe et al, 1981;Lotan and Nicolson, 1979;Lis and Sharon, 1973;Sharon and Lis, 1972).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The nine lectins used here were selected for their ability to distinguish the different types of cells present histochemically in the rat submandibular gland. The staining with UEA-I, LFA, PNA, LCA, DBA, and SBA (see Table 1) corresponded to previous studies (Schulte, 1987; Schulte and Spicer, 1984). Our ble to fine discrepancies in their preferred sugars with regard to both penultimate sugar and anomeric configuration (Spicer and Schulte, 1992;Watanabe et al, 1981;Lotan and Nicolson, 1979;Lis and Sharon, 1973;Sharon and Lis, 1972).…”
Section: Discussionsupporting
confidence: 88%
“…The application of labeled lectins in situ has provided information about the identity and distribution of specific glycoconjugates in secretory granules of various cell populations in different salivary glands (see Accili et al, 1992;Hosaka et al, 1986;Schulte, 1987;Schulte and Spicer, 1983Yamada and Shimizu, 1979). These studies have revealed a considerable heterogeneity in the secretory glycoconjugates present in salivary parenchymal cells.…”
Section: Introductionmentioning
confidence: 99%
“…These tendencies have been noted previously in salivary glands from other species by Schulte [9], who commented, "In some species, heterogeneity in glycoprotein structure was observed among morphologically similar cells within a gland". More recently Menghi et al [8] have noted differences in lectin binds between adjacent convoluted granular tubule cells in rats.…”
Section: Discussionsupporting
confidence: 80%
“…The many locations containing Galfi1,3GalNAc penultimate to sialic acid are recognized as those gaining PNA affinity after sialidase digestion (120,173,(175)(176)(177)180,183,184,219). Sites such as acini of hamster and ovine submandibular glands gain DBA reactivity after sialidase and therefore contain aGalNAc penultimate to sialic acid (178,184).…”
Section: Gzffoniz Szmpfk$olia Isoagglutinin I1 Exemplifies Another Lementioning
confidence: 99%
“…The application of a battery of lectins with varying specificities has revealed striking differences between GCs in the various cell types, in particular those of the gastrointestinal, genitourinary, respiratory, and nervous systems (9,30,31,36,56, 63,76,87,122,169,173,[175][176][177][178][179][180][181][182][183][184][185]201,212,213,219,221,235) which have been most thoroughly examined in this laboratory. These ddferences presumably can be attributed in some cases to differing glycopeptide content between cells and in other instances to cell-specific glycosylation of a given polypeptide (148,228) common to more than one cell type.…”
Section: Gcs D I -E R Among Cell Q P E S In An Individualmentioning
confidence: 99%